Workplace Violence And Effects On Turnover Intention And Job Commitment: A Pilot Study Among Healthcare Workers Ä°n Turkey - Aytac, Serpil; Dursun, Salih; Akalp, Gizem (European Scientific Journal, ESJ, 2016)
Workplace violence is not only a critical health and safety issue but also is a serious problem which can have devastating effects on the productivity of organizations and on the quality of life of employees. The purpose of this study was to investigate physical, verbal and sexual violence in the workplace and the effects on employees' commitment and job turnover intention in the health sector. A self-made questionnaire about workplace violence, a general condition, job commitment questionnaire and job turnover intention questionnaire were applied to 169 health employees to determine who had suffered workplace violence in the previous year. The relationship between job commitment, workplace violence and job turnover intention were investigated in two different hospitals. A statistically significant relationship was determined between job turnover intention and workplace violence. According to the data obtained, 57% of the respondents had been confronted with physical, verbal or sexual harrassment at least once in their professional life in the previous year. Additionally, 67% of the study respondents had witnessed one form or another of harassment behaviour. The t-test analysis results determined a significantly higher rate of job turnover intention for health workers who had been exposed to workplace violence than those who had not. The commitment rate of that group was determined to be low but the difference was not statistically significant.